Firearms accidents in sixteenth-century England - Gunn, SJ; Gromelski, T (Taylor & Francis, 2023)
Source material for the use of firearms in sixteenth-century England outside military contexts is sparse. This article uses coroners’ inquest reports to examine who used guns of what types, for what purposes, in different parts of England and at different phases of their diffusion. Artisans were prominent among early adopters, but by the end of the century yeomen were the most frequent gun owners. It shows what hazards guns with different firing mechanisms such as matchlocks and snaphances presented, the steps users took to mitigate such risks, and the severity of gunshot wounds, which caused two-thirds of victims of fatal firearms accidents to die instantly.